2017
DOI: 10.3389/fpls.2017.00594
|View full text |Cite
|
Sign up to set email alerts
|

De novo Sequencing and Transcriptome Analysis Reveal Key Genes Regulating Steroid Metabolism in Leaves, Roots, Adventitious Roots and Calli of Periploca sepium Bunge

Abstract: Periploca sepium Bunge is a traditional medicinal plant, whose root bark is important for Chinese herbal medicine. Its major bioactive compounds are C21 steroids and periplocin, a kind of cardiac glycoside, which are derived from the steroid synthesis pathway. However, research on P. sepium genome or transcriptomes and their related genes has been lacking for a long time. In this study we estimated this species nuclear genome size at 170 Mb (using flow cytometry). Then, RNA sequencing of four different tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Triterpenoid saponins primarily undergo synthesis via the MVA and MEP pathways, with the MVA pathway metabolism taking place primarily in the cytoplasm, and the MEP pathway taking place primarily in the plastid [17]. Chloroplasts are abundant in leaf samples less in stem but not in root samples, this may explain why we found that MEP pathway-associated genes were primarily upregulated in leaf samples, as has also previously been observed in Periploca sepium Bunge and Cymbopogon winterianus [43,44]. This fact may also explain why we observed a higher abundance of triterpenoid saponins in the leaves of A. elata relative to the root and stem tissues.…”
Section: Discussionsupporting
confidence: 80%
“…Triterpenoid saponins primarily undergo synthesis via the MVA and MEP pathways, with the MVA pathway metabolism taking place primarily in the cytoplasm, and the MEP pathway taking place primarily in the plastid [17]. Chloroplasts are abundant in leaf samples less in stem but not in root samples, this may explain why we found that MEP pathway-associated genes were primarily upregulated in leaf samples, as has also previously been observed in Periploca sepium Bunge and Cymbopogon winterianus [43,44]. This fact may also explain why we observed a higher abundance of triterpenoid saponins in the leaves of A. elata relative to the root and stem tissues.…”
Section: Discussionsupporting
confidence: 80%
“…Triterpenoids and sesquiterpenoids are biosynthesized via the MVA pathway, that takes place primarily in the cytoplasm, whereas monoterpenoids, diterpenoid, and tetraterpenoids are biosynthesized via the MEP pathway, that takes place primarily in the plastid [23]. Chloroplasts are abundant in leaf samples less in stem but not in root samples, this may explain why we found that MEP pathway-associated genes were primarily upregulated in leaf samples, as has also previously been observed in Periploca sepium Bunge and Cymbopogon winterianus [44,45]. This fact may also explain why we observed a higher abundance of triterpenoid saponins in the leaves of A. elata relative to the root and stem tissues.…”
Section: Discussionsupporting
confidence: 80%
“…Due to its high throughput and cost-effectiveness, next-generation sequencing technology, such as Illumina sequencing technology, has been widely applied to determine the transcriptomes of nonmodel plants. In recent years, many transcriptome data on nonmodel plants, including Cunninghamia lanceolata ( Huang et al, 2012 ; Qiu et al, 2013 ), Camellia sinensis ( Shi et al, 2011 ), Chinese bayberry ( Feng et al, 2012 ), Calotropis gigantea ( Muriira et al, 2015 ) and Periploca sepium ( Zhang et al, 2017 ), have been generated using Illumina sequencing technology. These transcriptome data provide valuable resources for further studies in these plants.…”
Section: Discussionmentioning
confidence: 99%